Ser-Povo-Movente: relações entre dança e patrimônio cultural - Mesquita, Estela Sá de (2024)
This work aims to understand the relationship between tangible and intangible cultural heritage based on the artistic interventions Ser-Povo-Movente (2022). This research was developed in the Postgraduate Program in Cultural Heritage at master's level, within the research line History and Cultural Heritage, and was born from questions about how the relationships are between dance and cultural heritage, and how these relationships take place. Using a bricolage methodology, the work aims to cover the areas of knowledge of dance and cultural heritage, as well as producing an audiovisual product, a documentary video artwork that seeks to cross artistic and creative issues with the aim of broadening knowledge about safeguarding heritage. Throughout the research, we came up with a Heritage Art Education proposal, based on the tripod of resonance (GONÇALVES, 2005 - 2019), dance in context (MARQUES, 2008) and incorporated practices (TAYLOR, 2008), which seeks a new way of seeing-doing-thinking about cultural heritage through art. The research as a whole, from the writing, the creative process of the artistic interventions SerPovo-Movente and the production of the video art "Corpos Ressoantes: o patrimônio local pelos olhos da arte" (Resounding Bodies: local heritage through the eyes of art) are shown as actions of an art and heritage education and aim to reach the community and lead them to reflect on the safeguarding of heritage.